Credit Risk Management and Loan Performance: Empirical Investigation of Micro Finance Banks of Pakistan - Ahmed, Sufi Faizan; Malik, Qaisar Ali (International Journal of Economics and Financial Issues, 2015)
The main aim of the paper is to evaluate the influence of credit risk management practices on loan performance while taking the credit terms, client appraisal, collection policy and credit risk control as the dimensions of the credit risk management practices. For statistical evaluation, the primary data in cross sectional form has been taken into consideration. The data is collected from the managerial level credit risk management staff of micro finance banking sector. Multiple regression analysis has been used for empirical relationship evaluation of the credit risk management practices on the performance of loan. The results of the analysis are showing that the credit terms and client appraisal have positive and significant impact on the loan performance, while the collection policy and credit risk control have positive but insignificant impact on loan performance. The study is helpful for the management to enhance the loan performance by focusing on the dimension of the credit risk management practices used in the study. Future aspects of the research have also been taken into account and elaborated. Keywords: Loan Performance; Credit Risk Management; Credit Terms; Credit Policy; Credit Risk Control; Loan Appraisal, Micro Finance. JEL Classifications: G20; G21; G30; G32